2014
DOI: 10.1371/journal.pone.0087330
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Quantitative Trait Locus Mapping Reveals Major Role of Epistasis on Yield of Rice

Abstract: Although rice yield has been doubled in most parts of the world since 1960s, thanks to the advancements in breeding technologies, the biological mechanisms controlling yield are largely unknown. To understand the genetic basis of rice yield, a number of quantitative trait locus (QTL) mapping studies have been carried out, but whole-genome QTL mapping incorporating all interaction effects is still lacking. In this paper, we exploited whole-genome markers of an immortalized F2 population derived from an elite ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…The phenotypic variance explained (PVE) by i-th QTL was estimated as PVE i ¼b 2 i s x i =s y , whereb is the estimated value of parameter β, σ x is the variance of the marker genotype, and σ y is the variance of climate sensitivity traits. PVE by all QTLs was estimated as PVE all ¼ s^y =s y , where s^y is the variance of the estimated value of the climate sensitivity traits, which is obtained from a multiple linear regression using significant QTLs as explanatory variables [45]. The prediction accuracy of significant QTLs was tested by correlating the observed and predicted values using five-fold cross validation.…”
Section: Qtl Analysismentioning
confidence: 99%
“…The phenotypic variance explained (PVE) by i-th QTL was estimated as PVE i ¼b 2 i s x i =s y , whereb is the estimated value of parameter β, σ x is the variance of the marker genotype, and σ y is the variance of climate sensitivity traits. PVE by all QTLs was estimated as PVE all ¼ s^y =s y , where s^y is the variance of the estimated value of the climate sensitivity traits, which is obtained from a multiple linear regression using significant QTLs as explanatory variables [45]. The prediction accuracy of significant QTLs was tested by correlating the observed and predicted values using five-fold cross validation.…”
Section: Qtl Analysismentioning
confidence: 99%
“…It is hence a biologically influential component contributing to the genetic architecture of quantitative traits (Mackay 2014). The influence of epistasis on genome-wide QTL mapping ranges from limited (e.g., Buckler et al 2009;Tian et al 2011) to high (e.g., Carlborg et al 2006;Würschum et al 2011;Huang et al 2014). These discrepancies can be explained by the complexities of the examined traits, which are controlled by many loci exhibiting small effects entailing a low QTL detection power.…”
mentioning
confidence: 99%
“…Our recent studies demonstrated that EBlasso has a broad range of applications such as whole-genome QTL mapping and pathway-based genome-wide association study (GWAS) [15,16,21]. When the number of possible effects is very large in QTL models with both main and epistatic effects, the computation time becomes a critical concern.…”
Section: Discussionmentioning
confidence: 99%
“…Both EBlasso and EBEN outperform other shrinkage methods including Lasso and MCMC-based Bayesian shrinkage methods in terms of PD and FDR. EBlasso has been applied to whole-genome QTL mapping [15] and pathway-based genome-wide association study (GWAS) [16], where linear regression models with millions of variables were inferred. However, optimized by a greedy coordinate ascent algorithm, the accuracy and computational speed may not be optimal for both methods.…”
Section: Introductionmentioning
confidence: 99%